Competing Interactions in DNA Assembly on Graphene - Akca, Saliha (Public Library of Science, 2011)
We study the patterns that short strands of single-stranded DNA form on the top graphene surface of graphite. We find that the DNA assembles into two distinct patterns, small spherical particles and elongated networks. Known interaction models based on DNA-graphene binding, hydrophobic interactions, or models based on the purine/pyrimidine nature of the bases do not explain our observed crossover in pattern formation. We argue that the observed assembly behavior is caused by a crossover in the competition between base-base pi stacking and base-graphene pi stacking and we infer a critical crossover energy of [Image: see text] eV. The experiments therefore provide a projective measurement of the base-base interaction strength.